THE CORRELATION BETWEEN INTEREST IN LISTENING TO ENGLISH SONGS AND ENGLISH PRONUNCIATION OF THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM, SRIWIJAYA UNIVERSITY INDRALAYA - MUTTAQIN, MUTTAQIN; HAMBALI, MUSLIH; HAYATI, RITA (Sriwijaya University Learning and Education International Conference, 2016)
The main purpose of this study was to describe whether or not the studentsâ interest in listening to English songs and their English pronunciation have a significant correlation. The method used in this study was a descriptive method. The population of this study was all of the English Education Study Program students of Sriwijaya University Indralaya. There were 172 students and the sample of this study was 85 students: Semester V and VII. Sampling method used in this study was purposive sampling method. The data were collected by means of questionnaire and test. To verify the hypotheses, the data obtained were analyzed by using the correlation analysis. The result of the analysis showed that most of the students who had high interest in listening to English songs had good pronunciation. There was statistically significant correlation between studentsâ interest in listening to English songs and their English pronunciation. The result of correlation analysis was 0.284, with p-value = 0.008. It meant that there was a significant correlation between studentsâ interest in listening to English songs and their English pronunciation.